Childhood Trauma of Domestic Violence and Violence in Further Intimate Relationship - Margaretha, Margaretha; Nuringtyas, Rahmaniar (UI Scholars Hub, 2013)
This study examines associations between childhood trauma of domestic violence (DV) with the involvement in intimate relationships violence (IRV), both as perpetrators and victims. The research was conducted in two studies focusing on the relationship between childhood trauma with, 1) aggression of DV perpetrators; and 2) violence experienced by victims of IRV. Study 1 was conducted on 62 male DV perpetrators in Surabaya and Sidoarjo, while the second study on 21 female non-direct DV victims. All samples were measured by using traumatic antecedents questionnaire (TAQ; Van der Kolk, Perry & Herman, 1991) and conflict tactics scales (CTS; Straus et al., 1996). The data is processed by using correlation and regression analyses with SPSS 18. Study 1 provides empirical evidence of long-term negative effects of childhood trauma on male perpetrators. Study 2 did not find a significant relation between traumatic experiences as a victim of DV with violence experienced in their current intimate relationships, but further study should consider this relationship can occur indirectly. It is hoped that this research could serve as a beginning of the development of a longitudinal study on the effects of DV on human psychophysics.